Satisfaction with life and human needs fulfillment - Abu Bakar, Aisyah; Mohamed Osman, Mariana (Malaysian Institute of Planners, 2021)
The two notions discussed in the paper are Life Satisfaction, under Subjective Well-Being (SWB) field; and Maslow hierarchy of human needs. Issue: Human needs satisfaction is not an all-or-nothing phenomenon. Individuals are not required to completely satisfy one need in order for the next need to appear in the hierarchy. Purpose: This paper aims to investigate the level of life satisfaction in relation to the difficulty and convenience of achieving human needs. Approach: Mann Whitney U-Tests were conducted to determine the mean of SWL across difficulty and convenient of fulfilling 24 human needs. These human needs are the necessities and life conditions commonly and widely struggled for. Findings: The ease with which the majority of human needs can be met increases life satisfaction significantly. The findings also revealed that for five human needs for which life satisfaction did not differ significantly, meeting these human needs was unlikely to influence life satisfaction. Maslow's Hierarchy of Needs classified these needs as biological and physiological needs, safety and security needs, and esteem needs.